Comparison of a Novel Surface Laser Scanning Anthropometric Technique to Traditional Methods for Facial Parameter Measurements. - Joe, Paula S.; Ito, Yasushi; Shih, Alan M.; Oestenstad, Riedar K.; Lungu, Claudiu T. (Journal of Occupational & Environmental Hygiene, 2012)
This study was designed to determine if three-dimensional (3D) laser scanning techniques could be used to collect accurate anthropometric measurements, compared with traditional methods. The use of an alternative 3D method would allow for quick collection of data that could be used to change the parameters used for facepiece design, improving fit and protection for a wider variety of faces. In our study, 10 facial dimensions were collected using both the traditional calipers and tape method and a Konica-Minolta Vivid9i laser scanner. Scans were combined using RapidForm XOR software to create a single complete facial geometry of the subject as a triangulated surface with an associated texture image from which to obtain measurements. A paired t-test was performed on subject means in each measurement by method. Nine subjects were used in this study: five males (one African-American and four Caucasian females) and four females displaying a range of facial dimensions. Five measurements showed significant differences (p < 0.05), with most accounted for by subject movements or amended by scanning technique modifications. Laser scanning measurements showed high precision and accuracy when compared with traditional methods. Significant differences found can be very small changes in measurements and are unlikely to present a practical difference. The laser scanning technique demonstrated reliable and quick anthropometric data collection for use in future projects in redesigning respirators.